Teaching the Aymara language on YouTube:: activism, attitudes and linguistic ideologies - Lovón, Marco (2023)
YouTube is a space for the dissemination of languages. In this article, we study the discourses on the teaching and learning of Aymara on the social network called YouTube, in videos created by institutions, independent groups and users in general in Bolivia. For this purpose, a discursive analysis of the comments made by cybernauts or followers is carried out. The research concludes that this is a case of linguistic activism in social networks, which is valued by their followers, while transmitting criticisms based on linguistic ideologies about language and its use.